2018
DOI: 10.1175/jpo-d-18-0139.1
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Coefficient in Stably Stratified Flows

Abstract: Turbulent mixing in the interior of the oceans is not as well understood as mixing in the oceanic boundary layers. Mixing in the generally stably stratified interior is primarily, although not exclusively, due to intermittent shear instabilities. Part of the energy extracted by the Reynolds stresses acting on the mean shear is expended in increasing the potential energy of the fluid column through a buoyancy flux, while most of it is dissipated. The mixing coefficient χm, the ratio of the buoyancy flux to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
(75 reference statements)
4
13
0
Order By: Relevance
“…C CT is traditionally called the mixing efficiency for CT (e.g., Oakey 1985), but it is actually a mixing coefficient (Gregg et al 2018;Kantha and Luce 2018). From Eqs.…”
Section: A2 Eddy Diffusivitymentioning
confidence: 99%
See 2 more Smart Citations
“…C CT is traditionally called the mixing efficiency for CT (e.g., Oakey 1985), but it is actually a mixing coefficient (Gregg et al 2018;Kantha and Luce 2018). From Eqs.…”
Section: A2 Eddy Diffusivitymentioning
confidence: 99%
“…(68 and 67), it is determined that R f is the rate of conversion of turbulent energy produced (from various energy sources) to buoyancy energy needed to mix stratification layers, and C CT is simply the ratio of consumed buoyancy energy to energy dissipation by viscosity. Hereafter, C CT is called the mixing coefficient (Gregg et al 2018;Kantha and Luce 2018).…”
Section: A2 Eddy Diffusivitymentioning
confidence: 99%
See 1 more Smart Citation
“…High‐resolution estimates from radar indicated that the range of γ is from 0.06 to 0.3 in the upper troposphere and lower stratosphere (Dole et al, ). A recent observational study suggests that the mixing coefficient is around 0.16–0.2 in both the atmosphere and ocean (Kantha & Luce, ).…”
Section: Introductionmentioning
confidence: 99%
“…For locally homogeneous, stationary and isotropic turbulence in dry (unsaturated) air produced by shear instabilities in a stably stratified background, ε and C 2 T are theoretically interrelated. ε can be estimated from C 2 T using [20,21]:…”
Section: Introductionmentioning
confidence: 99%